Induced Second Trimester Abortion and Associated Factors in Amhara Region Referral Hospitals. (30th March 2015) - Mulat, Amlaku; Bayu, Hinsermu; Mellie, Habtamu; Alemu, Amare
Abstract : Background . Although the vast majority of abortions are performed in the first trimester, still 10–15% of terminations of pregnancies have taken place in the second trimester period globally. As compared to first trimester, second trimester abortions are disproportionately contribute for maternal morbidity and mortality especially in low-resource countries where access to safe second trimester abortion is limited. The main aim of this study was to assess the prevalence and associated factors of induced second trimester abortion in Amhara region referral hospitals, northwest Ethiopia. Methods . Institution based cross-sectional study was conducted in Amhara region referral hospitals among 416 women who sought abortion services. Participants were selected using systematic sampling technique. Data were collected using pretested structured questionnaire through interviewing. After the data were entered and analyzed; variables which have P value < 0.2 in bivariate analysis, not colinear, were entered into multiple logistic regressions to see the net effect with 95% CI and P value < 0.05. Results . The prevalence of induced second trimester abortion was 19.2%. Being rural (AOR = 1.86 [95% CI = 1.11–3.14]), having irregular menstrual cycle (AOR = 1.76 [95% CI = 1.03–2.98]), not recognizing their pregnancy at early time (AOR = 2.05 [95% CI = 1.21–3.48]), and having logistics related problems (AOR = 2.37 [95% CI = 1.02–5.53]) were found to have statistically significant association with induced second trimester abortion. Conclusion . Induced second trimester abortion is high despite the availability of first trimester abortion services. Therefore, increase accessibility and availability of safe second trimester abortion services below referral level, counseling and logistical support are helpful to minimize late abortions.